Analyzing the Risk of Heavy Metal Pollution in Wastewater from the Open Drainage System in Rajshahi City, Bangladesh (Journal of Engineering Science, 2025)
This study evaluates heavy metal concentrations in drainage wastewater from 12 locations in Rajshahi City, assessing risks to aquatic ecosystems and public health using di-acid digestion method and atomic absorption spectrophotometry. The mean levels of heavy metals were Zn > Mn > Pb > Cr > Cu > Cd. Pb, Cr, and Cd levels exceeded the permissible limits set by the USEPA (0.006, 0.05, and 0.01 mg/L, respectively) and WHO (0.01, 0.05, and 0.003 mg/L, respectively), indicating significant contamination risks. Cu, Zn, and Mn levels, remained within permissible thresholds. All samples showed high metal concentrations with metal index values above 1. Notably, 75% of sites had HPI values over 100, 75% of the samples exhibited DC values over 3, 50% of the samples showed EWQI readings exceeding 0.3. The findings highlight the urgent need for improved wastewater treatment and sustainable water management practices to mitigate health and environmental risks.Journal of Engineering Science 16(1), 2025, 47-60